Detection of Mycoplasma wenyonii in cattle and transmission vectors by the loop-mediated isothermal amplification (LAMP) assay - Qiqi Song; Lixia Wang; Rui Fang; Muhammad Kasib Khan; Yanqin Zhou; Junlong Zhao (Tropical Animal Health and Production, 2012)

Breast Cancer Proteome Takes More Than Two to Tango on TRAIL: Beat Them at Their Own Game - Ammad Ahmad Farooqi; Sundas Fayyaz; Muhammad Tahir; Muhammed Javed Iqbal; Shahzad Bhatti (The Journal of Membrane Biology, 2012)

Agroforestry for Livelihood Security in Agrarian Landscapes of the Padma Floodplain in Bangladesh - Syed Ajijur Rahman; Muhammad Hasan Imam; Denyse J. Snelder; Terry Sunderland (Small-scale Forestry, 2012)

Zinc nutrition in rice production systems: a review - Hafeez-ur Rehman; Tariq Aziz; Muhammad Farooq; Abdul Wakeel; Zed Rengel (Plant and Soil, 2012)

Biofortification and estimated human bioavailability of zinc in wheat grains as influenced by methods of zinc application - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Tariq Aziz (Plant and Soil, 2012)

Sustained Delivery of IL-1Ra from Pluronic F127-Based Thermosensitive Gel Prolongs its Therapeutic Potentials - Muhammad Sajid Hamid Akash; Kanwal Rehman; Ni Li; Jian-Qing Gao; Hongying Sun; Shuqing Chen (Pharmaceutical Research, 2012)

Problems encountered in bicistronic IRES-GFP expression vectors employed in functional analyses of GC-induced genes - Muhammad Mansha; Muhammad Wasim; Christian Ploner; Abrar Hussain; Asma Abdul Latif; Muhammad Tariq; Anita Kofler (Molecular Biology Reports, 2012)

Chloroplast-encoded chlB gene from Pinus thunbergii promotes root and early chlorophyll pigment development in Nicotiana tabaccum - Shahid Nazir; Muhammad Sarwar Khan (Molecular Biology Reports, 2012)

In vitro callogenesis and detection of somaclonal variations in Plantago ovata L. - Tariq Mahmood; Aysha Jameel; Bilal Haider Abbasi; Faiza Munir; Syed Muhammad Saqlan Naqvi (Journal of Crop Science and Biotechnology, 2012)

In silico analysis reveals the presence of a large number of Ankyrin repeat containing proteins in Ectocarpus siliculosus - Niaz Mahmood; Mahdi Muhammad Moosa; Nahid Tamanna; Suprovath Kumar Sarker; Rifat Ara Najnin; Salma Sultana Alam (Interdisciplinary Sciences: Computational Life Sciences, 2012)

Antifungal effect and mechanism of chitosan against the rice sheath blight pathogen, Rhizoctonia solani - He Liu; Wenxiao Tian; Bin Li; Guoxing Wu; Muhammad Ibrahim; Zhongyun Tao; Yangli Wang; Guanlin Xie; Hongye Li; Guochang Sun (Biotechnology Letters, 2012)

Growth Control in Colon Epithelial Cells: Gadolinium Enhances Calcium-Mediated Growth Regulation - Durga Attili; Brian Jenkins; Muhammad Nadeem Aslam; Michael K. Dame; James Varani (Biological Trace Element Research, 2012)

Sea lamprey orient toward a source of a synthesized pheromone using odor-conditioned rheotaxis - Nicholas S. Johnson; Azizah Muhammad; Henry Thompson; Jongeun Choi; Weiming Li (Behavioral Ecology and Sociobiology, 2012)

Synthesis, crystal structure and β-glucuronidase inhibition activity of some new hydrazinecarboxamides and their 1,2,4-triazole derivatives - Muhammad Hanif; Imtiaz Khan; Nasim Hasan Rama; Shagufta Noreen; Muhammad Iqbal Choudhary; Peter G. Jones; Mazhar Iqbal (Medicinal Chemistry Research, 2012)

Synthesis, characterization and in vitro hydrolysis studies of ester and amide prodrugs of dexibuprofen - Zaman Ashraf; Muhammad Imran; Shahid Amin (Medicinal Chemistry Research, 2012)

Characterization of pilP, a gene required for twitching motility, pathogenicity, and biofilm formation of Acidovorax avenae subsp. avenae RS-1 - He Liu; Wen-Xiao Tian; Muhammad Ibrahim; Bin Li; Guo-Qing Zhang; Bo Zhu; Guan-Lin Xie (European Journal of Plant Pathology, 2012)

Biotoxicity Assessment of Pyrene in Soil Using a Battery of Biological Assays - Muhammad Imran Khan; Sardar Alam Cheema; Xianjin Tang; Chaofeng Shen; Shahbaz Talib Sahi; Abdul Jabbar; Joonhong Park; Yingxu Chen (Archives of Environmental Contamination and Toxicology, 2012)

Estrus response and follicular development in Boer does synchronized with flugestone acetate and PGF2α or their combination with eCG or FSH - Muhammad Modu Bukar; Rosnina Yusoff; Abd Wahid Haron; Gurmeet Kaur Dhaliwal; Mohd Azam Goriman Khan; Mohammed Ariff Omar (Tropical Animal Health and Production, 2012)

Factors affecting yield and composition of camel milk kept under desert conditions of central Punjab, Pakistan - Sibtain Ahmad; Muhammad Yaqoob; Muhammad Qamar Bilal; Muhammad Kasib Khan; Ghulam Muhammad; Li-Guo Yang; Muhammad Tariq (Tropical Animal Health and Production, 2012)

On the performance of a new bivariate pseudo Pareto distribution with application to drought data - Muhammad Mohsin; Gunter Spöck; Jürgen Pilz (Stochastic Environmental Research and Risk Assessment, 2012)

Divergences of MPF2-like MADS-domain proteins have an association with the evolution of the inflated calyx syndrome within Solanaceae - Jisi Zhang; Muhammad Ramzan Khan; Ying Tian; Zhichao Li; Simone Riss; Chaoying He (Planta, 2012)

Incidence of dsRNA Mycoviruses in a Collection of Aspergillus fumigatus Isolates - Muhammad F. Bhatti; Atif Jamal; Elaine M. Bignell; Michael A. Petrou; Robert H. A. Coutts (Mycopathologia, 2012)

Rb1/105 gene alterations and head and neck carcinogenesis - Maimoona Sabir; Ruqia Mehmood Baig; Ishrat Mahjabeen; Muhammad Saeed; Faraz Arshad Malik; Mahmood Akhtar Kayani (Molecular Biology Reports, 2012)

Molecular phylogeny of Pakistani riverine buffalo based on genetic variability of mitochondrial cytochrome b gene - Rashid Saif; Muhammad Wasim; Masroor Ellahi Babar (Molecular Biology Reports, 2012)

DDM1 (Decrease in DNA Methylation) genes in rice (Oryza sativa) - Hiromi Higo; Muhammad Tahir; Kazuya Takashima; Asuka Miura; Koichi Watanabe; Akemi Tagiri; Masashi Ugaki; Ryuji Ishikawa; Mitsugu Eiguchi; Nori Kurata; Takuji Sasaki; Eric Richards; et al. (Molecular Genetics and Genomics, 2012)

Structural characterization of carangid fish myoglobins - Muhammad Mehedi Hasan; Shugo Watabe; Yoshihiro Ochiai (Fish Physiology and Biochemistry, 2012)

Nexus between corruption and regional Environmental Kuznets Curve: the case of South Asian countries - Faiz Ur Rehman; Muhammad Nasir; Faiza Kanwal (Environment, Development and Sustainability, 2012)

Chronic toxicity of a laundry detergent to the freshwater flagellate Euglena gracilis - Azizullah Azizullah; Peter Richter; Muhammad Jamil; Donat-Peter Häder (Ecotoxicology, 2012)

Letter to the Editor: Cotton leaf curl Multan betasatellite strains cloned from Gossypium barbadense further supports selection due to host resistance - Muhammad Tehseen Azhar; Sohail Akhtar; Shahid Mansoor (Virus Genes, 2012)

Dracorhodin perchlorate inhibits PI3K/Akt and NF-κB activation, up-regulates the expression of p53, and enhances apoptosis - Azhar Rasul; Chuan Ding; Xiaomeng Li; Muhammad Khan; Fei Yi; Muhammad Ali; Tonghui Ma (Apoptosis, 2012)

Physicochemical Characterization of Complex Drug Substances: Evaluation of Structural Similarities and Differences of Protamine Sulfate from Various Sources - David Awotwe-Otoo; Cyrus Agarabi; David Keire; Sau Lee; Andre Raw; Lawrence Yu; Muhammad J. Habib; Mansoor A. Khan; Rakhi B. Shah (The AAPS Journal, 2012)

The MicroRNAs and their targets in the channel catfish (Ictalurus punctatus) - Muhammad Younas Khan Barozai (Molecular Biology Reports, 2012)

Antidepressant activity of carbamates and urea derivatives - Shahnaz Perveen; Nasreen Fatima; Muhammad Aitmaud Khan; Ahsana Dar; Khalid M. Khan; Nighat Afza; Wolfgang Voelter (Medicinal Chemistry Research, 2012)

Molecular simulations of bergenin as a new urease inhibitor - Mohammad Arfan; Hazrat Amin; Inamullah Khan; Muhammad Raza Shah; Hamidullah Shah; Amir Zada Khan; Syed Muhammad Ashhad Halimi; Nematullah Khan; Waqar Ahmad Kaleem; Mughal Qayum; Adnan Shahidullah; Muhammad Azam Khan (Medicinal Chemistry Research, 2012)

Synthesis and biological evaluation of some N4-substituted 5-nitroisatin-3-thiosemicarbazones - Humayun Pervez; Nazia Manzoor; Muhammad Yaqub; Faiz-ul-Hassan Nasim; Khalid M. Khan (Medicinal Chemistry Research, 2012)

Residual efficacy of thiamethoxam, Beauveria bassiana (Balsamo) Vuillemin, and diatomaceous earth formulation against Rhyzopertha dominica F. (Coleoptera: Bostrychidae) - Waqas Wakil; Tahira Riasat; Muhammad Ashfaq (Journal of Pest Science, 2012)

Stem cell-based delivery of Hypoxamir-210 to the infarcted heart: implications on stem cell survival and preservation of infarcted heart function - Ha Won Kim; Shujia Jiang; Muhammad Ashraf; Khawaja Husnain Haider (Journal of Molecular Medicine, 2012)

The low down on association mapping in hexaploid wheat (Triticum aestivum L.) - Muhammad Sajjad; Sultan Habibullah Khan; Abdul Mujeeb Kazi (Journal of Crop Science and Biotechnology, 2012)

Biomass partitioning and genetic analyses of salinity tolerance in sunflower (Helianthus annuus L.) - Saeed Rauf; Muhammad Shahzad; Jaime A. Teixeira da Silva; Ijaz Rasool Noorka (Journal of Crop Science and Biotechnology, 2012)

A brown alga Sargassum fulvellum facilitates neuronal maturation and synaptogenesis - Md. Abdul Hannan; Ji-Young Kang; Yong-Ki Hong; HyunSook Lee; Muhammad Tanvir Hossain Chowdhury; Jae-Suk Choi; In Soon Choi; Il Soo Moon (In Vitro Cellular & Developmental Biology - Animal, 2012)

Elemental contamination in urban parks of Rawalpindi/Islamabad—a source identification and pollution level assessment study - Sajid Iqbal; Mohammad Wasim; Muhammad Tufail; Mohammad Arif; Muhammad M. Chaudhry (Environmental Monitoring and Assessment, 2012)

Radium equivalent activity in the light of UNSCEAR report - Muhammad Tufail (Environmental Monitoring and Assessment, 2012)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)

A review of techniques and technologies for sand and dust storm detection - Muhammad Akhlaq; Tarek R. Sheltami; Hussein T. Mouftah (Reviews in Environmental Science and Bio/Technology, 2012)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Developing a web-based, collaborative PPGIS prototype to support public participation - Muhammad A. Butt; Songnian Li (Applied Geomatics, 2012)

Boron application through seed coating improves the water relations, panicle fertility, kernel yield, and biofortification of fine grain aromatic rice - Atique-ur Rehman; Muhammad Farooq (Acta Physiologiae Plantarum, 2012)

Root colonization and growth promotion of sunflower (Helianthus annuus L.) by phosphate solubilizing Enterobacter sp. Fs-11 - Muhammad Shahid; Sohail Hameed; Asma Imran; Saira Ali; Jan Dirk van Elsas (World Journal of Microbiology and Biotechnology, 2012)

Effect of management on reproductive performances of the Achai cattle in the Hindu Kush (Northern Pakistan) - Muhammad Saleem; Inam-ur Rahim; Henri Rueff; Momen Khan; Daniel Maselli; Urs Wiesmann; Sher Muhammad (Tropical Animal Health and Production, 2012)

Population structure and linkage disequilibrium in Lupinus albus L. germplasm and its implication for association mapping - Muhammad Javed Iqbal; Sujan Mamidi; Rubina Ahsan; Shahryar F. Kianian; Clarice J. Coyne; Anwar A. Hamama; Satya S. Narina; Harbans L. Bhardwaj (Theoretical and Applied Genetics, 2012)

Genetic structure and linkage disequilibrium pattern of a rapeseed (Brassica napus L.) association mapping panel revealed by microsatellites - Yingjie Xiao; Dongfang Cai; Wei Yang; Wei Ye; Muhammad Younas; Jiangsheng Wu; Kede Liu (Theoretical and Applied Genetics, 2012)

Maize (Zea mays L.) endogenous seed phosphorus remobilization is not influenced by exogenous phosphorus availability during germination and early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Alain Vives; Loïc Prud’homme; Sylvain Pellerin (Plant and Soil, 2012)

Aflatoxin contamination in different fractions of rice from Pakistan and estimation of dietary intakes - Shahzad Z. Iqbal; Muhammad R. Asi; Agustin Ariño; Noreen Akram; Muhammad Zuber (Mycotoxin Research, 2012)

Network bursting using experimentally constrained single compartment CA3 hippocampal neuron models with adaptation - Muhammad Dur-e-Ahmad; Wilten Nicola; Sue Ann Campbell; Frances K. Skinner (Journal of Computational Neuroscience, 2012)

The anti-arthritic and anti-oxidative effect of NBD (6-nitro-1,3-benzodioxane) in adjuvant-induced arthritis (AIA) in rats - Syed Uzair Ali Shah; Nadeem Ashraf; Zahid H. Soomro; Muhammad Raza Shah; Nurul Kabir; Shabana Usman Simjee (Inflammation Research, 2012)

Monitoring of cotton dust and health risk assessment in small-scale weaving industry - Muhammad Wajid Tahir; Muhammad Waseem Mumtaz; Shanza Tauseef; Muqadas Sajjad; Awais Nazeer; Nazish Farheen; Muddsar Iqbal (Environmental Monitoring and Assessment, 2012)

Determination of radioactive elements and heavy metals in sediments and soil from domestic water sources in northern peninsular Malaysia - Bashir G. Muhammad; Mohammad Suhaimi Jaafar; Azhar Abdul Rahman; Farouk Abdulrasheed Ingawa (Environmental Monitoring and Assessment, 2012)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)

Development of broad-spectrum insect-resistant tobacco by expression of synthetic cry1Ac and cry2Ab genes - Muhammad Nouman Sohail; Sohail Mehmood Karimi; Shaheen Asad; Shahid Mansoor; Yusuf Zafar; Zahid Mukhtar (Biotechnology Letters, 2012)

Effect of fulvic acids on lead-induced oxidative stress to metal sensitive Vicia faba L. plant - Muhammad Shahid; Camille Dumat; Jérôme Silvestre; Eric Pinelli (Biology and Fertility of Soils, 2012)

Seasonal variation in essential oil yield and composition from Thymus vulgaris L. during different growth stages in the south of Jordan - Mohammad S. Abu-Darwish; Muhammad H. Alu’datt; Abdel Rahman Al-Tawaha; Khalil Ereifej; Ali Almajwal; Nidal Odat; Wesam Al Khateeb (Natural Product Research, 2012)

Partial resistance to powdery mildew in German spring wheat ‘Naxos’ is based on multiple genes with stable effects in diverse environments - Qiongxian Lu; Åsmund Bjørnstad; Yan Ren; Muhammad Azeem Asad; Xianchun Xia; Xinmin Chen; Fang Ji; Jianrong Shi; Morten Lillemo (Theoretical and Applied Genetics, 2012)

In vitro propagation and characterization of phenolic content along with antioxidant and antimicrobial activities of Cichorium pumilum Jacq. - Wesam Al Khateeb; Emad Hussein; Lolita Qouta; Muhammad Alu’datt; Baker Al-Shara; Ahmed Abu-zaiton (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Screening sugarcane (Saccharum sp.) genotypes for salt tolerance using multivariate cluster analysis - Suriyan Cha-um; Sasiwimon Chuencharoen; Chareerat Mongkolsiriwatana; Muhammad Ashraf; Chalermpol Kirdmanee (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Building resilience to natural hazards in Indonesia: progress and challenges in implementing the Hyogo Framework for Action - Riyanti Djalante; Frank Thomalla; Muhammad Sabaruddin Sinapoy; Michelle Carnegie (Natural Hazards, 2012)

Novel and recurrent LDLR gene mutations in Pakistani hypercholesterolemia patients - Waqas Ahmed; Muhammad Ajmal; Ahmed Sadeque; Roslyn A. Whittall; Sobia Rafiq; Wendy Putt; Athar Khawaja; Fauzia Imtiaz; Nuzhat Ahmed; Maleeha Azam; Steve E. Humphries; Raheel Qamar (Molecular Biology Reports, 2012)

Novel quinolyl-thienyl chalcones and their 2-pyrazoline derivatives with diverse substitution pattern as antileishmanial agents against Leishmania major - Syed Umar Farooq Rizvi; Hamid Latif Siddiqui; Muhammad Nisar Ahmad; Matloob Ahmad; Mujahid Hussain Bukhari (Medicinal Chemistry Research, 2012)

Antimalarial and free radical scavenging activities of rhizomes of Polygonatum verticillatum supported by isolated metabolites - Haroon Khan; Muhammad Saeed; Murad Ali Khan; Inamullah Khan; Manzoor Ahmad; Naveed Muhammad; Afsar Khan (Medicinal Chemistry Research, 2012)

Comprehensive screening and selection of okra (Abelmoschus esculentus) germplasm for salinity tolerance at the seedling stage and during plant ontogeny - Ikram-ul- Haq; Asif Ali Khan; Iqrar Ahmad Khan; Muhammad Abubakkar Azmat (Journal of Zhejiang University-SCIENCE B, 2012)

Comparative adherence to oxybutynin or tolterodine among older patients - Tara Gomes; David Juurlink; Muhammad Mamdani (European Journal of Clinical Pharmacology, 2012)

Mineral bioavailability in grains of Pakistani bread wheat declines from old to current cultivars - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Muhammad Khawar Khan (Euphytica, 2012)

Effects of Vitamins, Probiotics, and Protein Level on Semen Traits and Some Seminal Plasma Macro- and Microminerals of Male Broiler Breeders After Zinc-Induced Molting - Rifat Ullah Khan; Zia-ur-Rahman; Ijaz Javed; Faqir Muhammad (Biological Trace Element Research, 2012)

Exophiala sp.LHL08 association gives heat stress tolerance by avoiding oxidative damage to cucumber plants - Abdul Latif Khan; Muhammad Hamayun; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Duk-Hwan Kim; In-Jung Lee (Biology and Fertility of Soils, 2012)

Leaf structural modifications for drought tolerance in some differentially adapted ecotypes of blue panic (Panicum antidotale Retz.) - Mansoor Hameed; Saima Batool; Nargis Naz; Tahira Nawaz; Muhammad Ashraf (Acta Physiologiae Plantarum, 2012)

An investigation of phenolic compounds from plant sources as trypsin inhibitors - Durre Shahwar; Muhammad Asam Raza; Shafiq-Ur-Rehman; Muhammad Athar Abbasi; Atta-Ur-Rahman (Natural Product Research, 2012)

Naturally occurring phytotoxins in allelopathic plants help reduce herbicide dose in wheat - Abdul Khaliq; Amar Matloob; Asif Tanweer; Muhammad Bismillah Khan (Natural Product Research, 2012)

Antimicrobial, antileishmanial and cytotoxic compounds from Piper chaba - Tarannum Naz; Ashik Mosaddik; Md. Motiur Rahman; Ilias Muhammad; Md. Ekramul Haque; Somi Kim Cho (Natural Product Research, 2012)

Measurement of radionuclides and absorbed dose rates in soil samples of Peshawar, Pakistan, using gamma ray spectrometry - Hasan M. Khan; Muhammad Ismail; Muhammad Abid Zia; Khalid Khan (Isotopes in Environmental and Health Studies, 2012)

Appraisal of radioactivity and associated radiation hazards in sand samples of four rivers of Punjab province, Pakistan - Khalid Khan; Muhammad Rizwan Khalid; Abdul Jabbar; Perveen Akhter (Isotopes in Environmental and Health Studies, 2012)

Responses to graded replacement of urea by maize steep liquor in diets for intensively fed lambs for meat production - Mahr-un- Nisa; Muhammad A. Shahzad; Clive J. C. Phillips; Muhammad Sarwar (Tropical Animal Health and Production, 2012)

Effect of varying dietary energy levels during the last trimester of pregnancy on subsequent first lactation performance in Sahiwal heifers - Muhammad Fiaz; Muhammad Abdullah; Muhammad Nasir; Khalid Javed; Masroor Ellahi Babar; Talat Naseer Pasha; Makhdoom Abdul Jabbar (Tropical Animal Health and Production, 2012)

Genetic Diversity and Population Structure of Ethiopian Chickpea (Cicer arietinum L.) Germplasm Accessions from Different Geographical Origins as Revealed by Microsatellite Markers - Gemechu Keneni; Endashaw Bekele; Muhammad Imtiaz; Kifle Dagne; Emana Getu; Fassil Assefa (Plant Molecular Biology Reporter, 2012)

A Decade of Experience: Cryptococcus gattii in British Columbia - Karen H. Bartlett; Po-Yan Cheng; Colleen Duncan; Eleni Galanis; Linda Hoang; Sarah Kidd; Min-Kuang Lee; Sally Lester; Laura MacDougall; Sunny Mak; Muhammad Morshed; Marsha Taylor; et al. (Mycopathologia, 2012)

Non-hypoxic stabilization of HIF-Iα during coordinated interaction between Akt and angiopoietin-1 enhances endothelial commitment of bone marrow stem cells - Vien Khach Lai; Muhammad Rizwan Afzal; Muhammad Ashraf; Shujia Jiang; Husnain Kh Haider (Journal of Molecular Medicine, 2012)

Multiple-point geostatistical modeling based on the cross-correlation functions - Pejman Tahmasebi; Ardeshir Hezarkhani; Muhammad Sahimi (Computational Geosciences, 2012)

A Multi-Mineral Natural Product Inhibits Liver Tumor Formation in C57BL/6 Mice - Muhammad N. Aslam; Ingrid Bergin; Madhav Naik; Anna Hampton; Ron Allen; Steven L. Kunkel; Howard Rush; James Varani (Biological Trace Element Research, 2012)

Letter to the Editor: Mastrevirus sequences in a begomovirus-infected plant - Muhammad Mubin; Shahid Mansoor; Rob W. Briddon (Virus Genes, 2012)

Prevalence of TP53 germ line mutations in young Pakistani breast cancer patients - Muhammad U. Rashid; Sidra Gull; Kashif Asghar; Noor Muhammad; Asim Amin; Ute Hamann (Familial Cancer, 2012)

High-density growth and crude protein productivity of a thermotolerant Chlorella vulgaris: production kinetics and thermodynamics - Shahid Mahboob; Abdul Rauf; Muhammed Ashraf; Tayyaba Sultana; Salma Sultana; Farhat Jabeen; Muhammad Ibrahim Rajoka; H. F. Alkahem Al-Balawi; Khalid A. Al-Ghanim (Aquaculture International, 2012)

Evaluation of Anticancer Drug-Loaded Nanoparticle Characteristics by Nondestructive Methodologies - David Awotwe-Otoo; Ahmed S. Zidan; Ziyaur Rahman; Muhammad J. Habib (AAPS PharmSciTech, 2012)

Diversity of potential pathogenicity and biofilm formation among Burkholderia cepacia complex water, clinical, and agricultural isolates in China - Muhammad Ibrahim; Qiaomei Tang; Yu Shi; Abdulwareth Almoneafy; Yuan Fang; Liuhu Xu; Wen Li; Bin Li; Guan-Lin Xie (World Journal of Microbiology and Biotechnology, 2012)

A cysteine-rich antimicrobial peptide from Pinus monticola (PmAMP1) confers resistance to multiple fungal pathogens in canola (Brassica napus) - Shiv S. Verma; William R. Yajima; Muhammad H. Rahman; Saleh Shah; Jun-Jun Liu; Abul K. M. Ekramoddoullah; Nat N. V. Kav (Plant Molecular Biology, 2012)

The novel 172 sheep (Ovis aries) microRNAs and their targets - Muhammad Younas Khan Barozai (Molecular Biology Reports, 2012)

Molecular characterization of oilseed rape accessions collected from multi continents for exploitation of potential heterotic group through SSR markers - Muhammad Younas; Yingjie Xiao; Dongfang Cai; Wei Yang; Wei Ye; Jiangsheng Wu; Kede Liu (Molecular Biology Reports, 2012)

Expression and glucocorticoid-regulation of “Bam”, a novel BH3-only transcript in acute lymphoblastic leukemia - Muhammad Mansha; Muhammad Wasim; Anita Kofler; Christian Ploner (Molecular Biology Reports, 2012)

A missense mutation (p.G274R) in gene ASPA causes Canavan disease in a Pakistani family - Rashida Hussain; Shakeela Daud; Naseebullah Kakar; Adeel Ahmad; Abdul Hameed Baloch; Abdul Malik Tareen; Muhammad Azam Kakar; Jamil Ahmad (Molecular Biology Reports, 2012)

Protective Function of Nicotinamide Against Ketamine-induced Apoptotic Neurodegeneration in the Infant Rat Brain - Najeeb Ullah; Ikram Ullah; Hae Young Lee; Muhammad Imran Naseer; Park Moon Seok; Jawad Ahmed; Myeong Ok Kim (Journal of Molecular Neuroscience, 2012)

Development of geomorphologic instantaneous unit hydrograph for a large watershed - Abdul Razzaq Ghumman; Muhammad Masood Ahmad; Hashim Nisar Hashmi; Mumtaz Ahmad Kamal (Environmental Monitoring and Assessment, 2012)

Effectiveness of three potential sources of resistance in wheat against Wheat streak mosaic virus under field conditions - Muhammad Fahim; Philip J. Larkin; Steve Haber; Steve Shorter; Paul F. Lonergan; Garry M. Rosewarne (Australasian Plant Pathology, 2012)

Climatic prediction of the terrestrial and coastal areas of Iraq - Salih Muhammad Awadh; Luma M. R. Ahmad (Arabian Journal of Geosciences, 2012)

Local calibration of remotely sensed rainfall from the TRMM satellite for different periods and spatial scales in the Indus Basin - Muhammad Jehanzeb Masud Cheema; Wim G. M. Bastiaanssen (International Journal of Remote Sensing, 2012)

Pure culture of Metarhizium anisopliae LHL07 reprograms soybean to higher growth and mitigates salt stress - Abdul Latif Khan; Muhammad Hamayun; Sumera Afzal Khan; Sang-Mo Kang; Zabta Khan Shinwari; Muhammad Kamran; Shafiq ur Rehman; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2012)

Effect of diet on preweaning performance of Sahiwal calves - Shaukat Ali Bhatti; Muhammad Faisal Ahmed; Peter Charles Wynn; David McGill; Muhammad Sarwar; Muhammd Afzal; Ehsan Ullah; Musarrat Abbas Khan; Muhammad Sajjad Khan; Russell Bush; Hassan Mahmood Warriach; Ahrar Khan (Tropical Animal Health and Production, 2012)

Application of the CSM-CERES-Rice model for evaluation of plant density and nitrogen management of fine transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Cecilia Manuela Tojo Soler; Hakoomat Ali; Muhammad Zia-Ul-Haq; Jakarat Anothai; Abid Hussain; Gerrit Hoogenboom; Mirza Hasanuzzaman (Precision Agriculture, 2012)

NutriTRAILomics in prostate cancer: time to have two strings to one’s bow - Ammad Ahmad Farooqi; Aamir Rana; Asma M. Riaz; Ammara Khan; Muhammad Ali; Sara Javed; Shahzeray Mukhtar; Sehrish Minhaj; Javeria Rafique Rao; Javairia Rajpoot; Rafia Amber; Fiza Asif Javed; et al. (Molecular Biology Reports, 2012)

O-GlcNAc modification of the anti-malarial vaccine candidate PfAMA1: in silico-defined structural changes and potential to generate a better vaccine - Nasir Uddin; Daniel C. Hoessli; Asma Butt; Afshan Kaleem; Zeeshan Iqbal; Imran Afzal; Muhammad Hammad; Zahra Zamani; Abdul Rauf Shakoori (Molecular Biology Reports, 2012)

The ribosomal protein L19 mRNA is induced by copper exposure in the swordtail fish, Xiphophorus helleri - Dwinna Aliza; Chiew-Lian Tey; Ida Shazrina Ismail; Meng-Kiat Kuah; Alexander Chong Shu-Chien; Tengku Sifzizul Tengku Muhammad (Molecular Biology Reports, 2012)

Association and expression quantitative trait loci (eQTL) analysis of porcine AMBP, GC and PPP1R3B genes with meat quality traits - Mehmet Ulas Cinar; Autchara Kayan; Muhammad Jasim Uddin; Elisabeth Jonas; Dawit Tesfaye; Chirawath Phatsara; Siriluck Ponsuksili; Klaus Wimmers; Ernst Tholen; Christian Looft; Heinz Jüngst; Karl Schellander (Molecular Biology Reports, 2012)

Synthesis and expression of recombinant interferon alpha-5 gene in tobacco chloroplasts, a non-edible plant - Muhammad Sarwar Khan; Farwa Nurjis (Molecular Biology Reports, 2012)

Association and expression study of MMP3, TGFβ1 and COL10A1 as candidate genes for leg weakness-related traits in pigs - Watchara Laenoi; Noppawan Rangkasenee; Muhammad Jasim Uddin; Mehmet Ulas Cinar; Chirawath Phatsara; Dawit Tesfaye; Armin M. Scholz; Ernst Tholen; Christian Looft; Manfred Mielenz; Helga Sauerwein; Klaus Wimmers; et al. (Molecular Biology Reports, 2012)

Extraction of DNA suitable for PCR applications from mature leaves of Mangifera indica L. - Muhammad Abubakkar Azmat; Iqrar Ahmad Khan; Hafiza Masooma Naseer Cheema; Ishtiaq Ahmad Rajwana; Ahmad Sattar Khan; Asif Ali Khan (Journal of Zhejiang University-SCIENCE B, 2012)

Environmental impact assessment (EIA): an overlooked instrument for sustainable development in Pakistan - Rashid Saeed; Ayesha Sattar; Zafar Iqbal; Muhammad Imran; Raziya Nadeem (Environmental Monitoring and Assessment, 2012)

Suppression of cytokine gene expression and improved therapeutic efficacy of microemulsion-based tacrolimus cream for atopic dermatitis - Manisha S. Lalan; Naresh C. Laddha; Jigar Lalani; Muhammad J. Imran; Rasheedunnisa Begum; Ambikanandan Misra (Drug Delivery and Translational Research, 2012)

Extraction, Cleanup, and Chromatographic Determination of Imidacloprid Residues in Wheat - Sajid Iqbal; Riaz Uddin; Sumayya Saied; Mubarik Ahmed; Muhammad Abbas; Sahar Aman (Bulletin of Environmental Contamination and Toxicology, 2012)

Polycyclic Aromatic Hydrocarbons (PAHs) in Vegetables and Fruits Produced in Saudi Arabia - Muhammad Waqar Ashraf; A. Salam (Bulletin of Environmental Contamination and Toxicology, 2012)

Lithological and structural control of Hattian Bala rock avalanche triggered by the Kashmir earthquake 2005, sub-Himalayas, northern Pakistan - Muhammad Basharat; Joachim Rohn; Dominik Ehret; Mirza Shahid Baig (Journal of Earth Science, 2012)

Sequencing and analysis of the complete genome of Newcastle disease virus isolated from a commercial poultry farm in 2010 - Muhammad Munir; Siamak Zohari; Muhammad Abbas; Mikael Berg (Archives of Virology, 2012)

RETRACTED ARTICLE: Bovine viral diarrhea virus nonstructural protein 5A is phosphorylated by cdc2 cyclin-dependent kinase in vitro - Muhammad Atif Zahoor; Saima Naim; Guangai Xue; Mariluz Arainga Ramirez (Archives of Virology, 2012)

Carnivore diet analysis based on next‐generation sequencing: application to the leopard cat ( Prionailurus bengalensis ) in Pakistan - WASIM SHEHZAD; TIAYYBA RIAZ; MUHAMMAD A. NAWAZ; CHRISTIAN MIQUEL; CAROLE POILLOT; SAFDAR A. SHAH; FRANÇOIS POMPANON; ERIC COISSAC; PIERRE TABERLET (Molecular Ecology, 2012)
Diet analysis is a prerequisite to fully understand the biology of a species and the functioning of ecosystems. For carnivores, traditional diet analyses mostly rely upon the morphological identification of undigested remains in the faeces. Here, we developed a methodology for carnivore diet analyses based on the next‐generation sequencing. We applied this approach to the analysis of the vertebrate component of leopard cat diet in two ecologically distinct regions in northern Pakistan. Despite being a relatively common species with a wide distribution in Asia, little is known about this elusive predator. We analysed a total of 38 leopard cat faeces. After a classical DNA extraction, the DNA extracts were amplified using primers for vertebrates targeting about 100 bp of the mitochondrial 12S rRNA gene, with and without a blocking oligonucleotide specific to the predator sequence. The amplification products were then sequenced on a next‐generation sequencer. We identified a total of 18 prey taxa, including eight mammals, eight birds, one amphibian and one fish. In general, our results confirmed that the leopard cat has a very eclectic diet and feeds mainly on rodents and particularly on the Muridae family. The DNA‐based approach we propose here represents a valuable complement to current conventional methods. It can be applied to other carnivore species with only a slight adjustment relating to the design of the blocking oligonucleotide. It is robust and simple to implement and allows the possibility of very large‐scale analyses.

Beta Glucan: A Valuable Functional Ingredient in Foods - Asif Ahmad; Faqir Muhammad Anjum; Tahir Zahoor; Haq Nawaz; Syed Muhammad Raihan Dilshad (Critical Reviews in Food Science and Nutrition, 2012)

Erratum to: Caprine pleuropneumonia in Beetal goats - Riaz Hussain; Muhammad Auon; Ahrar Khan; Muhammad Zargham Khan; Fazal Mahmood; Sajjad Ur-Rehman (Tropical Animal Health and Production, 2012)

Contagious caprine pleuropneumonia in Beetal goats - Riaz Hussain; Muhammad Auon; Ahrar Khan; Muhammad Zargham Khan; Fazal Mahmood; Sajjad Ur-Rehman (Tropical Animal Health and Production, 2012)

Genetic variation in strigolactone production and tillering in rice and its effect on Striga hermonthica infection - Muhammad Jamil; Tatsiana Charnikhova; Benyamin Houshyani; Aad van Ast; Harro J. Bouwmeester (Planta, 2012)

Assessment of flood hazard, vulnerability and risk of mid-eastern Dhaka using DEM and 1D hydrodynamic model - Muhammad Masood; Kuniyoshi Takeuchi (Natural Hazards, 2012)

Identification of MicroRNAs and their targets in Helianthus - Muhammad Younas Khan Barozai; Iftikhar Ahmed Baloch; Muhammad Din (Molecular Biology Reports, 2012)

Field evolved resistance to carbamates, organophosphates, pyrethroids, and new chemistry insecticides in Spodoptera litura Fab. (Lepidoptera: Noctuidae) - Sarfraz Ali Shad; Ali H. Sayyed; Sahar Fazal; Mushtaq A. Saleem; Syed Muhammad Zaka; Muhammad Ali (Journal of Pest Science, 2012)

Molecular marker assisted for recognition drought tolerant in some of bread wheat genotypes - Abdelaleim Ismail ElSayed; Muhammad Suhail Rafudeen (Journal of Crop Science and Biotechnology, 2012)

TLR4 polymorphisms and disease susceptibility - Mamoona Noreen; Muhammad Ali A. Shah; Sheeba Murad Mall; Shazia Choudhary; Tahir Hussain; Iltaf Ahmed; Syed Fazal Jalil; Muhammad Imran Raza (Inflammation Research, 2012)

Genetic mapping of an autosomal recessive postaxial polydactyly type A to chromosome 13q13.3–q21.2 and screening of the candidate genes - Umm-e-Kalsoom; Sulman Basit; Syed Kamran-ul-Hassan Naqvi; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2012)

Assessment of background levels of trace metals in water and soil from a remote region of Himalaya - Munir H. Shah; Javed Iqbal; Nazia Shaheen; Nadeem Khan; Muhammad Aziz Choudhary; Gulraiz Akhter (Environmental Monitoring and Assessment, 2012)

In vitro selection of resistant mutant garlic lines by using crude pathogen culture filtrate of Sclerotium cepivorum - Lin-qing Zhang; Zhi-hui Cheng; Muhammad Azam Khan; Yan-li Zhou (Australasian Plant Pathology, 2012)

Characterization of a thermostable and alkaline xylanase from Bacillus sp. and its bleaching impact on wheat straw pulp - Mahjabeen Saleem; Farheen Aslam; Muhammad Saleem Akhtar; Mohsin Tariq; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2012)

Seasonal prevalence of coccidiosis in industrial broiler chickens in Faisalabad, Punjab, Pakistan - Mian Muhammad Awais; Masood Akhtar; Zafar Iqbal; Faqir Muhammad; Muhammad Irfan Anwar (Tropical Animal Health and Production, 2012)

Role of post translational modifications and novel crosstalk between phosphorylation and O-beta-GlcNAc modifications in human claudin-1, -3 and -4 - Azeem Mehmood Butt; Ishaque Badshah Khan; Mureed Hussain; Muhammad Idress; Jun Lu; Yigang Tong (Molecular Biology Reports, 2012)

DNA typing of Pakistani cattle breeds Tharparkar and Red Sindhi by microsatellite markers - Amber Azam; Masroor Ellahi Babar; Sehrish Firyal; Aftab Ahmad Anjum; Nabeela Akhtar; Muhammad Asif; Tanveer Hussain (Molecular Biology Reports, 2012)

Identification of biotic and abiotic stress up-regulated ESTs in Gossypium arboreum - Muhammad Younas Khan Barozai; Tayyab Husnain (Molecular Biology Reports, 2012)

Studies in a consanguineous family reveal a novel locus for stuttering on chromosome 16q - Muhammad Hashim Raza; Rana Amjad; Sheikh Riazuddin; Dennis Drayna (Human Genetics, 2012)

An Alu repeat-mediated genomic GCNT2 deletion underlies congenital cataracts and adult i blood group - Guntram Borck; Naseebullah Kakar; Jochen Hoch; Katrin Friedrich; Jan Freudenberg; Gudrun Nürnberg; Rüstem Yilmaz; Shakeela Daud; Dost Muhammad Baloch; Peter Nürnberg; Johannes Oldenburg; Jamil Ahmad; et al. (Human Genetics, 2012)

Validation of molecular markers for resistance among Pakistani chickpea germplasm to races of Fusarium oxysporum f. sp. ciceris - Hina Ali; Muhammad Ahsan ul Haq; Tariq Mahmud Shah; Mehboob ur Rahman; Weidong Chen (European Journal of Plant Pathology, 2012)

Characterization of tannery effluent wastewater by proton-induced X-ray emission (PIXE) analysis to investigate their role in water pollution - Lubna Shakir; Sohail Ejaz; Muhammad Ashraf; Nisar Ahmad; Aqeel Javeed (Environmental Science and Pollution Research, 2012)

Erratum to: Nitrogen-efficient rice cultivars can reduce nitrate pollution - Khalid Rehman Hakeem; Altaf Ahmad; Muhammad Iqbal; Salih Gucel; Munir Ozturk (Environmental Science and Pollution Research, 2012)

Salt effect of nisin Z isolated from a marine fish on the growth inhibition of Streptococcus iniae, a pathogen of streptococcosis - Won-Seok Heo; Eun-Young Kim; Yu-Ri Kim; Muhammad Tofazzal Hossain; In-Soo Kong (Biotechnology Letters, 2012)

Stimulation of Fibroblast Proliferation by Insoluble Gadolinium Salts - Katherine Bleavins; Patricia Perone; Madhav Naik; Muneeb Rehman; Muhammad N. Aslam; Michael K. Dame; Sasha Meshinchi; Narasimharao Bhagavathula; James Varani (Biological Trace Element Research, 2012)

The unique role of siderophore in marine-derived Aureobasidium pullulans HN6.2 - Zhe Chi; Xing-Xing Wang; Zai-Chao Ma; Muhammad Aslam Buzdar; Zhen-Ming Chi (BioMetals, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Differential expression of vitellogenin mRNA and protein in response to rice resistance genes in two strains of Nilaparvata lugens (Hemiptera: Delphacidae) with different levels of virulence - Nirosha Samanmali Gamalath; Muhammad Tufail; Prem Nidhi Sharma; Naoki Mori; Makio Takeda; Chiharu Nakamura (Applied Entomology and Zoology, 2012)

Mutualistic association of Paecilomyces formosus LHL10 offers thermotolerance to Cucumis sativus - Abdul Latif Khan; Muhammad Hamayun; Ramalingam Radhakrishnan; Muhammad Waqas; Sang-Mo Kang; Yoon-Ha Kim; Jae-Ho Shin; Yeon-Sik Choo; Jong-Guk Kim; In-Jung Lee (Antonie van Leeuwenhoek, 2012)

FLOOD FREQUENCY ANALYSIS OF VARIOUS DAMS AND BARRAGES IN PAKISTAN - Shazia Afreen; Faqir Muhammad (Irrigation and Drainage, 2012)
Flood frequency analysis for six catchments in Pakistan is carried out. The gamma (G2) and generalized logistic (GLO) distributions are fitted. Based on goodness of fit tests, it is found that these distributions fit closely to the annual maximum peak flows except for Rasul and Trimmu. The quantile estimates based on GLO distribution are close to the observed values of annual maximum peak flows. A peak over threshold series model using GLO is also implemented for Rasul and Trimmu. Copyright © 2011 John Wiley & Sons, Ltd.

Risk factors associated with prevalence and major bacterial causes of mastitis in dromedary camels (Camelus dromedarius) under different production systems - Sibtain Ahmad; Muhammad Yaqoob; Muhammad Qamar Bilal; Ghulam Muhammad; Li-Guo Yang; Muhammad Kasib Khan; Muhammad Tariq (Tropical Animal Health and Production, 2012)

Synthesis, characterization, and urease inhibition of 5-substituted-8-methyl-2H-pyrido[1,2-a]pyrimidine-2,4(3H)-diones - Abdul Rauf; Sumaira Liaqat; Ashfaq M. Qureshi; Muhammad Yaqub; Aziz U. Rehman; Mahmood U. Hassan; Zahid H. Chohan; Faiz U. H. Nasim; T. Ben Hadda (Medicinal Chemistry Research, 2012)

Comparative adherence to oxybutynin or tolterodine among older patients - Tara Gomes; David N. Juurlink; Muhammad M. Mamdani (European Journal of Clinical Pharmacology, 2012)

Assessment of phenanthrene bioavailability in aged and unaged soils by mild extraction - Muhammad Imran Khan; Sardar Alam Cheema; Chaofeng Shen; Congkai Zhang; Xianjin Tang; Jiyan Shi; Xincai Chen; Joonhong Park; Yingxu Chen (Environmental Monitoring and Assessment, 2012)

Prevalence and genetic characterization of avian polyomavirus and psittacine beak and feather disease virus isolated from budgerigars in Mainland China - Qingye Zhuang; Jiming Chen; Muhammad Hassan Mushtaq; Jie Chen; Shuo Liu; Guangyu Hou; Jinping Li; Baoxu Huang; Wenming Jiang (Archives of Virology, 2012)